An approach to Magneto-Rheological Fluids and their technological applications (Research, Society and Development, 2024)
The objective of this work is to present documents published in the literature on magnetorheological fluids (FMRs), reports from 3 multinational companies operating in the (FMRs) market, pointing out: consumption by countries, abundantly, segments by type, by sector, CAGR (a of the ways most used by the market to analyze the potential return on an investment), and the potential in financial terms that this market aims to achieve by 2031. Magnetorheological fluids are materials belonging to the Materials Science class, and classified as Intelligent Matters and Composites. Generally they are arranged in paste form, with oil or water, magnetic particles that have an average diameter of several micrometers. The (FMR) can be reversibly controlled by a magnetic field and has the ability to change its state from liquid to semi-solid in milliseconds, making it attractive for technological applications. Starting from Rabinow (1947), several authors have been developing studies in the field of (FMRs) in the various areas of engineering, medicine and robotics in an integrated manner, including researchers who have synthesized magnetorheological fluids in external and internal laboratories (Universities), and presented recent advances for future commercial applications. Data collection for this work is based on qualitative, documentary research with narrative review. The world market for magnetorheological fluids has been very prominent over the last decade, with negative points being: high investment cost in relation to other fluids, scarcity of raw materials, lack of technical knowledge on the part of the consumer in relation to the advanced properties of the material consumer for technological applications.